Structural Balancing vs Horizon Flattening on Seismic Data: Example from Extensional Tectonic Setting - SN Fathiyah Jamaludin, AH Abdul Latiff, DP Ghosh, . (2015)
Two techniques which are structural balancing and horizon flattening have been applied in this work to verify and validate the seismic interpretation performed on a few extracted 2D seismic cross-sections. Both techniques are useful to provide a mean of understanding what had happened or at least to imagine what had happened during the time of deposition for each of the interpreted horizons.